Karimun Regency Library's Efforts to Increase Interest in Reading through Smart Cars - Evelin, Joana; Nadeak, Irma Dolsye Maria; Igiasi, Teguh Setiandika (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research began with the researcher's relationship regarding the role of smart cars on the literacy of students in Karimun Besar. This qualitative research using the case study method aims to analyze students regarding smart cars. Researchers use the theory of structural functionalism by Talcot Parrson to analyze the function of smart cars in increasing literacy in the current era. The results of this research show that the presence of smart cars makes students broaden their knowledge. The role of smart cars is to increase literacy. The use of increasing children's interest in reading can be seen after the arrival of the Karimun Regional Archives and Library Office smart car arrived at the school. The library aims to make users interested, so that interest increases in visitors. The efforts made by the Karimun district library and archives service include having a mobile library service to schools in Karimun.